Artificial intelligence : 29th Benelux Conference, BNAIC 2017, Groningen, the Netherlands, November 8-9, 2017, Revised selected papers /: 29th Benelux Conference, BNAIC 2017, Groningen, the Netherlands, November 8-9, 2017, Revised selected papers. (2018) - Unknown
No abstract available